2009
DOI: 10.1016/j.geb.2008.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative behavior and the frequency of social interaction

Abstract: We report results from an experiment that examines play in an indefinitely repeated, two-player Prisoner's Dilemma game. Each experimental session involves N subjects and a sequence of indefinitely repeated games. The main treatment consists of whether agents are matched in fixed pairings or matched randomly in each indefinitely repeated game. Within the random matching treatment, we elicit player's strategies and beliefs or vary the information that players have about their opponents. Contrary to a theoretica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
182
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 230 publications
(196 citation statements)
references
References 20 publications
11
182
1
2
Order By: Relevance
“…Our findings are consistent with earlier findings that subjects cooperate and punish in the last round of the standard version of these experiments, as there too there is 7 Duffy and Ochs [2009] show that subjects play non-cooperatively in a prisoner's dilemma with stochastic end date and anonymous random matching, while they play cooperatively in a control with fixed pairs. See Kandori [1992] and Ellison [1993] for calculations of the discount factor required for contagion to be an equilibrium in infinitely-repeated games with anonymous random matching.…”
Section: Introductionsupporting
confidence: 92%
“…Our findings are consistent with earlier findings that subjects cooperate and punish in the last round of the standard version of these experiments, as there too there is 7 Duffy and Ochs [2009] show that subjects play non-cooperatively in a prisoner's dilemma with stochastic end date and anonymous random matching, while they play cooperatively in a control with fixed pairs. See Kandori [1992] and Ellison [1993] for calculations of the discount factor required for contagion to be an equilibrium in infinitely-repeated games with anonymous random matching.…”
Section: Introductionsupporting
confidence: 92%
“…On the other hand, the existence of strategic cooperation is suggested by differences in cooperation between random-matching and fixed-matching treatments, which have been found in bribery games (Abbink 2004), principal-agent games (Cochard and Willinger 2005), trust games (Huck et al 2006), conflict games (Lacomba et al 2010), prisoner's dilemma games (Duffy and Ochs 2009), gift-exchange games (Gächter and Falk 2002), and public good games (Croson 1996;Keser and van Winden 2000). In contrast, Andreoni (1988) finds more cooperation under random matching (for an explanation of these mixed results see Andreoni and Croson 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Schwartz, Young, and Zvinakis (2000), Camera andCasari (2009), andGong andYang (2010) all find that observing an opponent's history of play significantly increases cooperation, though Duffy and Ochs (2009) do not observe this effect in their data. In all of these studies, subjects are aware that their actions will be revealed to future opponents.…”
Section: Related Literaturementioning
confidence: 95%